Sosialisasi Anti Perundungan (Bullying) Bagi Peserta Didik SDN 1 Batu Putih, Kecamatan Sekotong, Kabupaten Lombok Barat - Siti Yulianah M. Yusuf; Basuki Sri Hermanto; Nia Kurniati; Syaumudinsyah; Fitriah Kartini (AMMA : Jurnal Pengabdian Masyarakat, 2024)
School is the second educational environment after the family. Schools play an important role in the psychological, social and emotional development of children as pupils. There's a lot of bullying nowadays done by kids around the school. The impact is concerned not only physical disturbance but also mental. Preventing negotiations is a shared responsibility for schools, parents, teachers, and society as a whole. Through dedication to the massacre, we endeavour to educate the younger generations in particular the children of the students in SDN 1 Batu Putih, Sekotong district, West Lombok district about negotiation / bullying. This activity is expected to benefit students in preventing bullying in the school surroundings.